Новые виды рода систоле - Systole Walk. (Hymenoptera, Eurytomidae) из семян шалфеев (Salvia spp.) - Зерова, М.Д. (Вестник зоологии, 1968)
The author describes two new species of the genus Systole Walk. Systole nikol-skayae sp. n. found in seeds of Salvina nutans L. and Salvia nemorosa L. and Systole salviae sp. n. found in seeds of Salvia scabiosifolia Lam.
Systole nikolskayae sp. n. (fig. 1, a— o)
Female. Body short, compact, black, tops of all the femurs and front tibia pale-yellow. Head and thorax with a very thin fine-locular sculpture. At the front head trans-verse. Antennae short, first joint of a funicle slightly elongated, 2-4 transverse. A club long, massive. Thorax wide, rather prominent. Intermediate segment very sloping, in the centre — fine-dotted, on sides — with big locules. Abdomen — short-oval, equal to thorax length. The length is 1.7-1.9 mm. Male. It differs from the female by a more slender body. Antennae with short prominent scape, funicle joints roundish, prominent, successively shorten from the first to the last; a club not long, compact. Stalk is equal to 2/3 of the length of posterior coxae. Abdomen short, roundish.
Systole salviae sp. n. (fig. 2, a — 2/c)
Male. Body rather slender, black. Front tibia and partially femurs of all the legs — yellow. Head and thorax with thin fine-locular sculpture. Head wider than thorax, considerably narrowed to the lower end. Antennae with strongly prominent scape, fu-nicle joints elongated, approximately of the same length, a club very long. An interme-diate segment in the centre with rare wrinkles, Jocular on sides. A stalk is equal to the length of posterior coxae. Abdomen rather long, equal approximately to a half thorax length. The types of the described species are kept in the collection of the Institute of Zoo-logy, Academy of Sciences, Ukrainian SSR.